2016
DOI: 10.1371/journal.pone.0164366
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Hospital Inpatient Care: Effects of Trust, Medical Insurance and Perceived Quality of Care

Abstract: ObjectiveDeteriorations in the patient-provider relationship in China have attracted increasing attention in the international community. This study aims to explore the role of trust in patient satisfaction with hospital inpatient care, and how patient-provider trust is shaped from the perspectives of both patients and providers.MethodsWe adopted a mixed methods approach comprising a multivariate logistic regression model using secondary data (1200 people with inpatient experiences over the past year) from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
109
3
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 57 publications
11
109
3
10
Order By: Relevance
“…At the time of this study (data collection), the country was at the peak of her economic recession, which contributed to the upward review of the bills of the hospital almost shortly before the onset of this study. Recessions are known to cause contractions in economic growth, leading to fiscal crises for governments, compromising their ability to fund medical care and eventually causing employers and hospital managements to alter their service charges to sustain the hospital expenditure and service provision [25]; and patient satisfaction has been reported to be negatively associated with higher levels of hospital medical expenditure [26]. Other major factor responsible for the relative low satisfaction in this area is the fact that almost all the patients sampled have their bills paid directly by themselves or their family members; majority were not under the national health insurance scheme.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of this study (data collection), the country was at the peak of her economic recession, which contributed to the upward review of the bills of the hospital almost shortly before the onset of this study. Recessions are known to cause contractions in economic growth, leading to fiscal crises for governments, compromising their ability to fund medical care and eventually causing employers and hospital managements to alter their service charges to sustain the hospital expenditure and service provision [25]; and patient satisfaction has been reported to be negatively associated with higher levels of hospital medical expenditure [26]. Other major factor responsible for the relative low satisfaction in this area is the fact that almost all the patients sampled have their bills paid directly by themselves or their family members; majority were not under the national health insurance scheme.…”
Section: Discussionmentioning
confidence: 99%
“…It improves trust, loyalty and decreases the number of lawsuits. Service quality is often regarded as the antecedent of patient satisfaction ( Irfan (2012, Speight 2005, Zarei et al (2012, Shan et al, (2016). For these reasons patient satisfaction survey is an effective tool that provides information and insight on patients' views of the services they receive.…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…Özlü and Uzun ( 2015) found that there were differences in patient satisfaction with nursing care in surgery clinics in different hospitals in turkey related to educational background, profession, the hospital in which the patients stay and previous hospital experience . Shan (2016) found that lack of trust was behind patient dissatisfaction with hospital inpatient care in Heilongjiang in China.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Patient satisfaction is assumed that the values in certain services provided by the officer are attached to the patient's memory and will differ in each individual so this will increase the patient's willingness to recommend, increase trust, loyalty and reduce the number of complaints, therefore quality of service often considered a preliminary to patient satisfaction (Shan et al, 2016) Fenny et al, (2014 stated that quality of health service factors are important for the realization of patient satisfaction although different people may judge the same services differently because they are influenced by the expectations and characteristics of each individual. e. The effect of accreditation status to patient satisfaction This study showed that accreditation status of community health center has a contextual influence on the variation of patient satisfaction in general with ICC= 13.79%.…”
Section: Factors Affecting To Quality Ofmentioning
confidence: 99%